CRITERIA OF THE CLINICAL OUTCOME OF THE ACUTE CORONARY SYNDROME INTO THE PROGRESSIVE STENOCARDIA AT THE HOSPITAL STAGE - M. G. Alieva (Юг России: экология, развитие)
Aim. The aim of this study is to develop a prognostic flowchart for the clinical outcome of acute coronary syndrome into progressive stenocardia at the hospital stage.Materials and methods. The studies were carried out basing on the results of the survey of 68 patients admitted to the infarction department of the Republican Clinical Hospital of the Center for Special Emergency Medical Care in Makhachkala in 2015 which correspond to the basic principles of the Declaration of Helsinki - Ethical Principles for Medical Research Involving Human Subjects as amended in 2000. The severity of acute heart failure by Killip, electrocardiography (ECG) and EchoCG studies were conducted according to generally accepted standards.Findings. The research allowed developing the model of the prognostic block diagram. All indicators of relative risk (RR) for the studied indicators were reliable. Calculations of the values of RR were carried out according to the most frequent ranges of concentration of indicators of the number of patients. The greatest statistical power was possessed by concentration ranges for cardiac markers - TP-I from 0.6 to 1.1 ng / ml and BNP-32 from 60 to 110 pg / ml; For inflammation markers - IL-1β from 1.4 to 2.4 pg / ml and TNF-α from 2.6 to 3.6 pg / ml; For endothelial dysfunction markers - NO from 10 to 15 μmol / l and ET from 3.3 to 4.3 fmol / ml; For immunomarkers, cardiolipin antibodies (CA) from 1 to 3 U / ml and NP from 17 to 26 nmol / l. Measurement of these parameters at the initial stage of admission of patients with acute coronary syndrome (ACS) to the hospital (the starting point of reference) and the statement of positive results (the point of separation) made it possible to predict the outcome of ACS into the progressive stenocardia (end point) with high probability.Conclusion. In the calculation of relative risk, were taken into account the concentration ranges that were most frequently encountered among the number of patients. This methodological approach allowed to significantly increase the reliability of the prognosis, thus we reasonably recommend the use of the proposed flowchart in the clinical practice.